Distribution of Poh Roh Asset Due to Divorce in Gayo Lues Community Aceh - Lifa Datun Nisa; Darmawan Darmawan; Muhammad Adli (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
This research was conducted in Kute Lintang Village, Blangkejeren Sub-district of Gayo Lues Regency, which discussed the poh roh assets, according to the Gayo Lues customary law, a discussion about the distribution of poh roh assets in the Gayo Lues community. This research applied descriptive method with a normative juridical approach to obtain secondary data, sociological juridical approach, and field research.  The distribution system of poh roh assets due to divorce can be done in 2 (two) ways, namely by consensus and carried out through jeuma opat. The conciliation process carried out by divorced husband and wife ussually carried out by way of deliberations involving family relatives from both huband and wife. Whereas dispute resolution through jeuma opat emphasizes family aspects through deliberations to reach consensus, so none from the husband or wife feels defeated or won and jeuma opat knows about the origin of the assets obtained during their marriages, which are inherited assets, where inheritance is obtained from heirs of husband and wife and where are the poh roh assets, then simplify jeuma opat in terms of dividing the poh roh assets if there is a divorce because it already knows the origin of the divorced husband and wife's assets. Legal Consequences if the poh roh assets not shared After the divorce in Gayo Lues is the status of the poh roh assets will be not clear, it means that the husband and wife can no longer separate which is inherited from poh roh assets, even between the inheritance and the poh roh assets has been mixed, so it is very it is difficult to determine the status of property in a marriage.